Service-Dominant Logic-Based Business Models for Circularity in the Smartphone Industry - Saleem, Paras (My University, 2026)
The growing environmental impact of smartphones and the rapid accumulation of electronic waste have intensified interest in circular economy solutions within the consumer electronics sector. Although practices such as refurbishment, repair, and recommerce are increasingly adopted, existing research has largely examined circularity from technological or operational perspectives, offering limited insight into the value-creation logics that sustain these models over time. Addressing this gap, this thesis explores how Service-Dominant Logic (SDL)–based business models enable circularity in the smartphone industry. Using SDL as the core theoretical framework, the study conceptualises circularity as a service-driven and relational process that emerges through value co-creation, resource integration, and multi-actor service ecosystems. A qualitative multiple-case research design is employed, based on document analysis of three leading circular smartphone platforms: Swappie, Refurbed, and Back Market. These cases capture diverse configurations of service-oriented circular business models operating within evolving regulatory and market contexts. The findings indicate that circularity in the smartphone sector is not achieved at the product level alone but through coordinated service systems that stabilise markets for second-hand devices. Circular outcomes depend on selectively organised service ecosystems that establish governance structures and participation rules; on the integration of physical devices with operant resources such as technical expertise, digital infrastructures, and logistics capabilities; and on active customer involvement in value co-creation through usage, trade-in, and trust-based interactions. Value co-creation is shown to function not only as an outcome of circular systems but also as a feedback mechanism that reshapes ecosystem structures and resource configurations over time. The study contributes theoretically by extending SDL to circular business model research and by reframing circularity as a dynamic service system. Practically, it offers insights for firms and policymakers seeking to design and scale service-oriented circular models in the smartphone industry.
Keywords: Circularity, Service-based Business Models, Service Dominance Logic, Value co-creation, Resource Integration, Service Ecosystems.